Advanced social work with children and families - Cocker, Christine; Allain, Lucille (Exeter Learning Matters, 2011)
Practice and legislation in child and family social work is always changing and has once again come under the spotlight. This text contextualises the bureaucratization and managerialism of modern social work whilst also covering the advanced and complex skills necessary for competent social work practice in this area.
Includes bibliographical references (pages 161-179) and index.
Keywords: Social work with children -- Great Britain; Family social work -- Great Britain